2016
DOI: 10.1080/14659891.2016.1208778
|View full text |Cite
|
Sign up to set email alerts
|

Emergency service use is common in the year before death among drug users who die from an overdose

Abstract: AimsThis study compares the characteristics of those who were or were not attended by the emergency services in the year before death. It describes the reasons for emergency service attendance and the prevalence of such attendance. It reports the number of days between the last emergency service attendance and death and examines contact with other health and social services and the association of this with emergency service attendance. Finally, it examines the association between frequency of emergency service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…3 Patients admitted to an ED for an overdose are at greatly elevated risk for a subsequent nonfatal overdose and overdose death. [4][5][6] Thus, the ED encounter has been presented as both a critical and opportune time to prevent recurrent opioid overdoses and death through increased uptake in addiction treatment and provision of other harm reduction and recovery services. 7 However, to our knowledge, there is limited evidence on the most effective ways to promote engagement in treatment after discharge from an ED.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Patients admitted to an ED for an overdose are at greatly elevated risk for a subsequent nonfatal overdose and overdose death. [4][5][6] Thus, the ED encounter has been presented as both a critical and opportune time to prevent recurrent opioid overdoses and death through increased uptake in addiction treatment and provision of other harm reduction and recovery services. 7 However, to our knowledge, there is limited evidence on the most effective ways to promote engagement in treatment after discharge from an ED.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, more opioid overdose deaths were recorded in the United States than in any prior year, and opioid-related visits to US emergency departments (EDs) increased 4-fold from 2008 to 2018 . Patients admitted to an ED for an overdose are at greatly elevated risk for a subsequent nonfatal overdose and overdose death . Thus, the ED encounter has been presented as both a critical and opportune time to prevent recurrent opioid overdoses and death through increased uptake in addiction treatment and provision of other harm reduction and recovery services .…”
Section: Introductionmentioning
confidence: 99%
“…24 Frequent hospital and ED use has been linked to greater risk of experiencing both nonfatal and fatal overdoses, 5,6 and both US and international research has found ED utilization to be highest in the months preceding and after overdose. 79…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Frequent hospital and ED use has been linked to greater risk of experiencing both nonfatal and fatal overdoses, 5,6 and both US and international research has found ED utilization to be highest in the months preceding and after overdose. [7][8][9] Given that persons at risk of overdose interact frequently with the ED, intervening at this point of contact could be an effective overdose prevention strategy. EDs are especially important intervention points because patients who come into contact with the ED because of overdose or other conditions may not otherwise access the health care system.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…An examination of these patients compared with those who overdosed in other types of locations can be useful in further establishing the relative benefits of overdosing in a staffed location. Given that many who have died of an overdose had been in contact with ambulance services in the year before they died 27 , the use of ambulance data can be an important tool for exploring overdose events. Our aims were to use ambulance data as a proxy source to describe the demographic, clinical, and temporal characteristics of opioid overdoses.…”
Section: Introductionmentioning
confidence: 99%